DISCLOSING AGENT FROM RED DRAGON FRUIT PEEL AS DENTAL PLAQUE INDICATOR - Purbaningtyas, Eky; Yuliani, Fifin; Ananda, Arief Putra; Sari, Rezmelia (Odonto : Dental Journal, 2020)
Background: Red dragon fruit peel mucoadhesive gel has the potential to dye dental plaque. The colour of a transparent dental plaque can be seen with visualize using dyes (disclosing agent). One of the natural products containing dyestuff betacyanin, namely the peel of the red dragon (Hylocereus polyrhizus). This research aimed to review the peels of red dragon betacyanin (Hylocereus polyrhizus) in the mucoadhesive gel formula as an alternative disclosing agent.Method: Research is done with the manufacture of thick peels of a red dragon extract with the maceration methods. In clinical trials carried out an application red dragon fruit peel mucoadhesive gel 10%, concentration 15 % and Three-Tone Plaque Disclosing Gel. The assessment of plaque was carried out using the O’leary method. Result: The results obtained were analyzed by the t-test method. The mean of plaque index scores with red dragon fruit peel mucoadhesive gel concentrations of 10% (22.08), 15% (26,29) and Three-Tone Plaque Disclosing Gel (66,21; 64,20). The effectiveness of the gel with a concentration of 10% is 33.87%, and 15% concentration is 40.32%. Conclusion: The mucoadhesive gel of red dragon fruit peel has the potential to colour dental plaque.